2022
DOI: 10.1111/oik.08839
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod influences the shape and scaling of freshwater phytoplankton responses to light and temperature

Abstract: Light fluctuations are ubiquitous, exist across multiple spatial and temporal scales, and directly affect the physiology and ecology of photoautotrophs. However, the indirect effects of light fluctuations on the sensitivity of organisms to other key environmental factors are unclear. Here, we evaluate how photoperiod regime (period of time each day where organisms receive light), a dynamic element of aquatic ecosystems, can influence the interactive effects of temperature and irradiance (intensity of light) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
1
6
1
Order By: Relevance
“…It is important to note that beyond the illustrative examples described here, other environmental variables also interact in complex ways altering performance of a variety of biological systems and therefore highlighting the relevance of considering such complex multifactorial scenarios in variability research. Temperature has been shown to interact with irradiance affecting phytoplankton growth rate, and the effect of this interaction is shaped by the photoperiod regime (light fluctuations, Theus et al 2022). Furthermore, other relevant interactive effects of environmental factors on performance have been highlighted in the literature, like the combined effects of temperature and oxygen concentration on marine invertebrates and fish metabolism and physiology (Pörtner 2010; Vaquer‐Sunyer and Duarte 2011; Roman et al 2019), or temperature and salinity effects on mussel's vital rates (Guzmán‐Agüero et al 2013), but less is known about these interactions under fluctuating conditions.…”
Section: Relevant Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that beyond the illustrative examples described here, other environmental variables also interact in complex ways altering performance of a variety of biological systems and therefore highlighting the relevance of considering such complex multifactorial scenarios in variability research. Temperature has been shown to interact with irradiance affecting phytoplankton growth rate, and the effect of this interaction is shaped by the photoperiod regime (light fluctuations, Theus et al 2022). Furthermore, other relevant interactive effects of environmental factors on performance have been highlighted in the literature, like the combined effects of temperature and oxygen concentration on marine invertebrates and fish metabolism and physiology (Pörtner 2010; Vaquer‐Sunyer and Duarte 2011; Roman et al 2019), or temperature and salinity effects on mussel's vital rates (Guzmán‐Agüero et al 2013), but less is known about these interactions under fluctuating conditions.…”
Section: Relevant Frameworkmentioning
confidence: 99%
“…For environmental variables other than temperature the information is sparse, and approaches differ among variables, but some comparisons between constant and fluctuating environments are available. Variable light affects phytoplankton performance differently than constant light (Shatwell et al 2012; Theus et al 2022) and the effect of fluctuations depends on the average irradiance and the period of fluctuations (i.e., the part of the response curve that is analyzed and the frequency of fluctuations) (Litchman 1998, 2000; Shatwell et al 2012). Experimental studies using salinity gradients showed that marine mussels' vital rates (filtration, respiration, among others) might have nonlinear response curves (Guzmán‐Agüero et al 2013; Peteiro et al 2018), but the effects of salinity fluctuations have not been addressed using the performance framework.…”
Section: Challenges Of Integrating Inferences From Experimental Data ...mentioning
confidence: 99%
See 1 more Smart Citation
“…We predicted that phytoplankton abundance would increase under the longer (late-season) photoperiod due to longer light exposure (Seyfabadi et al, 2011;Shatwell et al, 2012;Tang & Vincent, 2000;Theus et al, 2022), but we had no a priori predictions for periphyton and zooplankton.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have sought to improve the link between TPCs and predictions of fitness in natural environments (Fey et al, 2019 ; Khelifa et al, 2019 ; Kremer et al, 2018 ; Sinclair et al, 2016 ), these have mainly focused on the effects of life‐history, behaviour and physiology. Recent work has shown that thermal performance curves can also respond to changes in the availability of resources such as food or light (Theus et al, 2022 ; Thomas et al, 2017 ) further challenging the practice of making a prediction based on ‘idealized’ TPCs. Building on the work of Brett et al ( 1969 ) and Brett ( 1971 ), who showed that the individual growth of salmon was optimized at lower temperatures as the availability of food declined, Thomas et al ( 2017 ) found that the optimal temperature for phytoplankton population growth occurred at lower temperatures under reduced nutrient availability and used a model to derive a mechanistic understanding of this shift.…”
Section: Introductionmentioning
confidence: 99%